Characteristics and Distribution of Mandibular Fractures Due to External Causes: A Retrospective Study - Dmitry José de Santana SARMENTO; Alessandro Leite CAVALCANTI; Jalber Almeida dos SANTOS (Association of Support to Oral Health Research (APESB), 2007)
Purpose: To investigate the characteristics and distribution of the cases of mandibular fractures due to external causes treated at the Hospital Regional de Campina Grande, PB, Brazil, between January 2002 and December 2006. Method: For such purpose, an indirect review of 691 medical-hospital patient files of the Service of Oral and Maxillofacial Surgery were reviewed. A total of 59 (8.5%) files referred to mandibular fracture victims. The following variables were analyzed: gender, age range, time of occurrence (date and hour), etiology, presence of associated fractures, type of treatment and time of hospitalization. Results: The results showed that males were more frequently affected than females (83.1%), with predominance in the 21-30 age range (40.7%). Most cases were treated on Saturdays and Sundays (40.6%) and at night (30.5%). Falls, (28.8%), interpersonal violence (23.7%) and motorcycle accidents (23.7%) were the main etiologies. Five patients (8.5%) presented fractures in other facial bones and the most frequent treatment was the intermaxillary retention with stainless steel wire (50.8%). The mean hospitalization time was 5.28 days.Conclusions: The prevalence of mandibular fractures is higher in the male gender, during the third decade of life; falls were the main etiologic factor and most cases occurred during the weekend.